The importance of labour administrative records: some notes about the impact of Legislative Decree 1246 in the job of Labour Administration - De Lama Laura, Manuel Gonzalo (2020)
From the implementation of Legislative Decree 1246, which sought economic recovery, the modification and repeal of certain substantive labor standards was determined, which led to the elimination of some formal obligations that the employer had in charge of the Administrative Labour Authority, as was the presentation of labor training modality agreements, contracts subject to modality, among others.Based on this, this article will analyze the purpose of these eliminated administrative requirements and the negative repercussions that these new provisions would produce within the Labour Administration.For these purposes, we will first analyze what legal basis lies in the importance of labor administrative records, and then identify the implications, which are derived from the exemption of some business obligations for the Administrative Labor Authority, in relation to certain functions and objectives of the latter.